2019
DOI: 10.1111/jphd.12351
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of self‐reported oral health in the Black Women's Health Study

Abstract: Objectives To describe the self‐reported oral health of participants in the Black Women's Health Study (BWHS), a national cohort of 59,000 Black women, and to assess factors associated with this self‐report. Methods Annual follow‐up of the BWHS cohort occurs via surveys. The 2011 questionnaire included oral health self‐report items, on which 38,573 respondents had complete data. Sample characteristics were summarized using descriptive statistics. We assessed correlations with several covariates by estimating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…The strong gradient between self-rated oral health and specific oral conditions observed in the PATH Study is consistent with other findings, including studies with clinically measured outcomes and in diverse populations defined by age and race/ethnicity (Thomson et al 2012; Cozier et al 2020; Lundbeck et al 2020). The concordance plausibly reflects the co-occurrence of shared risk factors for multiple aspects of poor oral health (Sheiham and Watt 2000).…”
Section: Discussionsupporting
confidence: 89%
“…The strong gradient between self-rated oral health and specific oral conditions observed in the PATH Study is consistent with other findings, including studies with clinically measured outcomes and in diverse populations defined by age and race/ethnicity (Thomson et al 2012; Cozier et al 2020; Lundbeck et al 2020). The concordance plausibly reflects the co-occurrence of shared risk factors for multiple aspects of poor oral health (Sheiham and Watt 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Bindu et al [ 37 ] also found that pregnant women placed lower priority for oral and fear for dental services were reasons for delaying dental services. Also, higher parity has been associated with number teeth present, functional tooth units of natural teeth regardless of socio-demographic and behavioural variables [ 38 , 39 ]. Women of lower parity in Nigeria tended to have better oral health [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We use this measure for three reasons. First, the measure aligns with tooth loss, oral pain and discomfort, and dentists' professional ratings of oral health [55][56][57]. Thus, the measure provides a valid, reliable, and cost-efficient way to assess oral health [58][59][60].…”
Section: Dependent Variablementioning
confidence: 96%
“…Thus, the measure provides a valid, reliable, and cost-efficient way to assess oral health [58][59][60]. Second, the measure is a strong predictor of other health measures including hypertension, diabetes, and obesity [56,61]. Third, the item we use is commonly used in the research literature and has been validated for study population [62][63][64].…”
Section: Dependent Variablementioning
confidence: 99%